Analysis Of Vibration Characteristics In Centrifugal Pump - Nayagam, Brian Pravinnayagam Adie (Universiti Sains Malaysia, 2021)
Centrifugal pumps are rotating machinery used in various applications such as in agriculture, petroleum, construction, industry and also used in sewage and waste. Centrifugal pump operating with continuous operation may result in pump failures due to some faults in the centrifugal pump which will require expensive maintenance and service for the centrifugal pump. This work aims to investigate the vibration characteristics in centrifugal pump operating with healthy (normal) condition and with the presence of mechanical fault due to loose mounting and cavitation due to a blocked filter. Vibration signals from the centrifugal pump are obtained by using an accelerometer which was placed on the top and side of the centrifugal pump for identifying horizontal and vertical vibration of the pump. The vibration signal is analyzed using time domain and Fast Fourier Transform (FFT) spectrum. Time-domain analysis shows that the healthy pump operated under minimum flow rate condition produces higher vibration amplitude than the maximum flow condition. The vibration level is higher at a high operating speed. The blocked filter and loose mounting pump produce a higher vibration amplitude than the healthy pump for both the minimum flow rate and maximum flow rate. Fast Fourier Transform (FFT) spectrum analysis denotes the fault frequencies produced by these types of faults and shows that the FFT analysis is helpful in detecting the fault frequencies produced by the blocked filter and loose mounting and can be used for fault detection in a centrifugal pump.